2021
DOI: 10.1177/1533033821990017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Induction Chemotherapy Plus Concurrent Chemoradiotherapy and Concurrent Chemoradiotherapy Alone in Locally Advanced Nasopharyngeal Carcinoma

Abstract: Purpose: Induction chemotherapy plus concurrent chemoradiotherapy and concurrent chemoradiotherapy alone are both standard treatment regimens for managing locally advanced nasopharyngeal carcinoma. However, the results of comparisons between them in clinical trials vary. Therefore, we designed this meta-analysis to illustrate their advantages and disadvantages in patients with locally advanced nasopharyngeal carcinoma. Methods: We thoroughly searched the PubMed, EMBASE, and Cochrane Library databases and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Therefore, the treatment side effects and other related profiles are not revealed in the results. However, the current meta‐analytic results reconfirmed the significant benefits for survival of patients with locoregionally advanced NPC seen in previous meta‐analyses 26–35 . Therefore, the benefits of ICT for the survival condition of locoregionally advanced NPC might be consistent and persuasive.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, the treatment side effects and other related profiles are not revealed in the results. However, the current meta‐analytic results reconfirmed the significant benefits for survival of patients with locoregionally advanced NPC seen in previous meta‐analyses 26–35 . Therefore, the benefits of ICT for the survival condition of locoregionally advanced NPC might be consistent and persuasive.…”
Section: Discussionsupporting
confidence: 79%
“…Our meta‐analysis enrolled the latest studies evaluating ICT with CCRT for patients with locoregionally advanced NPC 18,19,24 . The results might be more updated than previous meta‐analyses 26–31 . We also analyzed more survival indicators than the previous meta‐analyses 27–29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study by Zhang et al ( 7 ) has suggested that for specific patients (NPC with chronic hepatitis B infection), IC does not provide a significant efficacy gain for CCRT, but increases the toxicity and liver burden. A meta-analysis is the best way to resolve the controversies ( 8 ). Therefore, we conducted this meta-analysis to further explore the efficacy and safety of IC + CCRT vs. CCRT alone, and we also tried to perform subgroup analysis of different stages of LNC, different age levels, and different IC chemotherapy regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, several prospective studies have shown that IC consistently results in higher response and exerts a pronounced effect on survival and distant metastasis ( 4 7 ). A meta-analysis also showed that the addition of IC to CRT improved progression-free survival (PFS) and overall survival (OS) ( 8 10 ). Based on these findings, platinum-based IC, herein the combination of docetaxel (DTX), cisplatin (CDDP), and fluorouracil (TPF) and gemcitabine (GEM)+CDDP (GP) followed by CRT, are now considered standard therapy over CRT alone for this patient population ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%